Establishment of Infection by Pasteurella Multocida B:2 in Calves - Chau, Thi Huyen Trang (2009)
Infection by Pasteurella multocida B:2 leading to haemorrhagic septicaemia in cattle and buffaloes has been reported in many countries and is considered to be one of the most economically important livestock diseases in Southeast Asia, including Malaysia. This study was conducted to investigate the role of intranasal vaccination on colonization of wild-type P. multocida B:2 and gdhA derivative of P. multocida B:2 onto the nasal mucosa and lungs of calves. Three healthy local calves, about 6 months of age, were used. The first and second calves were exposed intranasal twice at two-week interval with 3.2 × 107 CFU/mL of live wild-type P. multocida B:2 and 7.0 × 107 CFU/mL of live gdhA derivative of P. multocida B:2, respectively. The third calf was untreated. Two weeks after the second exposure, all calves were killed and in vitro explants of the lung and nasal mucosa were immediately prepared before they were challenged with 0.5 mL of the inoculum containing 109 CFU/mL of live wild-type P. multocida B:2 and incubated at 37C. At 2, 6, and 12 hours post-challenge, three explants from each calf were removed and processed for scanning electron microscopic (SEM) examination to determine the rate of colonization. In vitro colonization of wild-type P. multocida B:2 onto the lung explants of calves exposed to either the wild-type or gdhA derivative of P. multocida B:2 was significantly (p<0.01) less severe than the untreated calf when mild to moderate colonization were observed. However, colonization onto the nasal mucosa showed no significant difference (p>0.05) between the three calves throughout the entire 12-hour study period. Following intratracheal introduction to high dose of wild-type (3.3 × 1010 CFU/mL) and gdhA derivative of P. multocida B:2 (5.4 × 109 CFU/mL) into calves, the phagocytic efficiency of alveolar macrophages were determined at 48 h post-inoculation. Wild-type P. multocida B:2 resulted in clinical signs typical of haemorrhagic septicaemia, which include dullness, fever, mucous nasal discharge and salivation. Subcutaneous oedema was obvious at the lower jaw, neck and brisket areas. Post-mortem examination was concentrated primarily on the respiratory tract. The lungs, trachea and epiglottis were congested and oedematous while the associated lymph nodes were congested with petechial haemorrhages. These changes were not observed in calves inoculated with gdhA derivative of P. multocida B:2. There was significant (p<0.05) difference in the phagocytic efficiency of alveolar macrophages and neutrophils between calves inoculated with wild-type (45.1 ± 4.1%) and those inoculated with gdhA derivative (57.3 ± 3.4%) of P. multocida B:2. In conclusion, the intranasal exposures to either wild-type or the gdhA derivative of P. multocida B:2 was significantly reduced colonization of the respiratory tract by wild-type P. multocida B:2. Similarly, intra-tracheal exposures of calves to the gdhA derivative of P. multocida B:2 failed to establish the disease due to the more efficient phagocytosis by the neutrophils and macrophages compared to the wild-type P. multocida B:2. Therefore, the gdhA derivative of P. multocida B:2 was found to be easily eliminated by phagocytosis and was unable to survive for long period of time in the host.